Forecasting of Sudan Inflation Rates using ARIMA Model - Abdulrahman, Badreldin Mohamed Ahmed; Ahmed, Abuzar Yousef Ali; Abdellah, Abderhim Elshazali Yahia (International Journal of Economics and Financial Issues, 2018)
This Study forecasted the inflation rates in Sudan. Annual time series data for the period 1970-2016 has been used in the analysis, by using Box-Jenkins method and ARIMA model. Data were obtained from Central Bureau of Statistics in Sudan. The results showed that, there is a convergence between predictive values and actual values during the period (1970-2016). Hence, there inflation rates in Sudan will increase in the coming years (2017-2026). Keywords: Inflation, Box-Jenkins, ARIMA, Model, Forecasting JEL Classifications: E17, E31